Muscle Cell Morphogenesis, Structure, Development and Differentiation Processes Are Significantly Regulated during Human Ovarian Granulosa Cells In Vitro Cultivation - Dompe, Claudia; Kranc, Wiesława; Jopek, Karol; Kowalska, Katarzyna; Ciesiółka, Sylwia; Chermuła, Błażej; Bryja, Artur; Jankowski, Maurycy; Perek, Joanna; Józkowiak, Małgorzata; Moncrieff, Lisa; Hutchings, Greg; et al. (Journal of clinical medicine, 2020)
Granulosa cells (GCs) have many functions and are fundamental for both folliculogenesis and oogenesis, releasing hormones and communicating directly with the oocyte. Long-term in vitro cultures of GCs show significant stem-like characteristics. In the current study, RNA of human ovarian granulosa cells was collected at 1, 7, 15 and 30 days of long-term in vitro culture. Understanding the process of differentiation of GCs towards different cell lineages, as well as the molecular pathways underlying these mechanisms, is fundamental to revealing other possible stemness markers of this type of cell. Identifying new markers of GC plasticity may help to understand the aetiology and recurrence of a wide variety of diseases and health conditions and reveal possible clinical applications of the ovarian tissue cells, affecting not only the reproductive ability but also sex hormone production. Granulosa cells were the subject of this study, as they are readily available as remnant material leftover after in vitro fertilisation procedures and exhibit significant stem-like characteristics in culture. The change in gene expression was investigated through a range of molecular and bioinformatic analyses. Expression microarrays were used, allowing the identification of groups of genes typical of specific cellular pathways. This candidate gene study focused on ontological groups associated with muscle cell morphogenesis, structure, development and differentiation, namely, “muscle cell development”, “muscle cell differentiation”, “muscle contraction”, “muscle organ development”, “muscle organ morphogenesis”, “muscle structure development”, “muscle system process” and “muscle tissue development”. The results showed that the 10 most upregulated genes were keratin 19, oxytocin receptor, connective tissue growth factor, nexilin, myosin light chain kinase, cysteine and glycine-rich protein 3, caveolin 1, actin, activating transcription factor 3 and tropomyosin, while the 10 most downregulated consisted of epiregulin, prostaglandin-endoperoxide synthase 2, transforming growth factor, interleukin, collagen, 5-hydroxytryptmine, interleukin 4, phosphodiesterase, wingless-type MMTV integration site family and SRY-box 9. Moreover, ultrastructural observations showing heterogeneity of granulosa cell population are presented in the study. At least two morphologically different subpopulations were identified: large, light coloured and small, darker cells. The expression of genes belonging to the mentioned ontological groups suggest the potential ability of GCs to differentiate and proliferate toward muscle lineage, showing possible application in muscle regeneration and the treatment of different diseases.